THE DIVERSITY OF CORPORATE GOVERNANCE MODELS. OVERVIEW AT THE COUNTRY LEVEL - MOHAMMED SUBHI AL ESSAWI; PETRE BREZEANU (Annals of the University of Petrosani: Economics, 2011)
This paper concentrates on the key features of corporate governance models; first, it highlights the correlation between corporate governance and the economic welfare; secondly it sets forth the characteristics of the models at the country level. The focus is placed on the correlations between the key elements that are intrinsic to the governance evolution in time.